Morphea as Part of the Dermatological Manifestation of Celiac Disease: Case Presentation and Review of the Literature - Gadi Howard; Amir Horev; Benzion Samueli; Baruch Yerushalmi (Karger Publishers, 2021)
Celiac disease is an immune-mediated disease, affecting multiple systems and organs including several dermatological conditions. Morphea, or localized scleroderma, is also an immune-mediated condition, in which an association with celiac disease has not thus far been recognized. We present an interesting case report of a 10-year-old child with a recent diagnosis of celiac disease presenting with morphea. Following treatment and adherence to a gluten-free diet, the morphea rapidly resolved. We suggest a possible relationship between the two entities and give a brief review of the relevant literature. We suggest that morphea might be one of the many dermatological manifestations of celiac disease, with possible implications for the need to screen patients with morphea for celiac disease.